2003
DOI: 10.1002/chem.200305238
|View full text |Cite
|
Sign up to set email alerts
|

SSZ‐53 and SSZ‐59: Two Novel Extra‐Large Pore Zeolites

Abstract: The syntheses, structure solutions, and physicochemical and catalytic characterizations of the novel zeolites SSZ-53 and SSZ-59 are described. SSZ-53 and SSZ-59 were synthesized under hydrothermal conditions with the [1-(4-fluorophenyl)cyclopentylmethyl]trimethyl ammonium cation and 1-[1-(4-chlorophenyl)cyclopentylmethyl]-1-methyl azocanium cation, respectively, as structure-directing agents. The framework topology of SSZ-53 was solved with the FOCUS method, and the structure of SSZ-59 was determined by model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
112
1
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 41 publications
6
112
1
14
Order By: Relevance
“…Using large and rigid OSDAs, different extra-large-pore zeolites presenting mono-directional 14-ring channels [3][4][5], multi-dimensional extra-large channels [6,7] and even mesoporous zeolites [8,9] have been synthesized. In these cases, the zeolite crystallization occurs through the interaction of single organic molecular units with the inorganic sources present in the synthesis gel.…”
Section: Introductionmentioning
confidence: 99%
“…Using large and rigid OSDAs, different extra-large-pore zeolites presenting mono-directional 14-ring channels [3][4][5], multi-dimensional extra-large channels [6,7] and even mesoporous zeolites [8,9] have been synthesized. In these cases, the zeolite crystallization occurs through the interaction of single organic molecular units with the inorganic sources present in the synthesis gel.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, novel materials and new synthesis methodologies are always the interesting topics in the field of molecular sieves. [4][5][6][7][8] Molecular sieves are normally synthesized under hydrothermal condition using amorphous gel as the starting material. However, it is sometimes found that the crystallization of one molecular sieve phase is followed by in situ transformation into another phase.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] [19]). However, the use of these materials is rather limited owing to the difficult separation of nanosized zeolite crystals from the reaction mixture,[3] the complexity of the templates used for the synthesis of ultralarge-pore zeolites, [6][7][8][9] and the relatively low thermal and hydrothermal stability of ordered mesoporous materials. [17][18][19][20][21][22][23][24][25][26][27][28] More recently, mesoporous zeolites from nanosized carbon templates have also been successfully synthesized, [29][30][31][32] but their industrial applications are still limited by the complexity of the synthetic procedure involved and the hydrophobicity of the carbon templates.…”
mentioning
confidence: 99%
“…However, relatively small individual micropores in zeolites such as Beta, ZSM-5, and Y strongly influence mass transport to and from the active sites located within them, severely limiting the performance of industrial catalysts. [1,2] To overcome this problem, various strategies have been successfully pursued, such as the synthesis of nanosized zeolites, [3] ultralarge-pore zeolites and zeolite analogues (VPI-5, [4] JDF-20, [5] UTD-1, [6,7] CIT-5, [8] SSZ-53, [9] ECR-34, [10] UCSB, [11] ITQ-21, [12] IM-12, [13] and SU-M, [14,15] among others), and ordered mesoporous materials (e.g. MCM-41, [17] SBA-15, [18] and FSM-16, [19]).…”
mentioning
confidence: 99%